Expanding solar energy capacity to power the transition to heat pumps - Alexander Roth; Carlos David Gaete Morales; Adeline Guéret; Dana Kirchem; Martin Kittel; Wolf-Peter Schill (DIW Weekly Report, 2022)
Increasing the use of heat pumps is an important measure for reducing carbon emissions in the heating sector as well as natural gas imports. This report uses an electricity sector model to investigate the effects of an accelerated expansion of the heat pump stock on the German electricity sector in 2030. Adding around six million heat pumps would increase electricity demand by nine percent in 2030; to meet this demand with solar energy, photovoltaic capacity would have to be expanded by 23 percent. Natural gas imports could be reduced by 15 percent. From a macroeconomic perspective, the higher the price of natural gas, the more advantageous it becomes to increase the use of heat pumps. Accelerating the transition to heat pumps, however, requires an ambitious and coordinated policy program that also focuses on the production capacity of heat pumps and on providing advanced training to workers - a kind of "Apollo program" for heat pumps.
Keywords: Q42; Q48; 330; heat pumps; natural gas; sector coupling; energy modeling